The global burden of disease study and Population Health Metrics - Grant M A Wyper (Population Health Metrics)
Abstract This year marked the launch of the Global Burden of Disease (GBD) 2021 study, the first presentation of the study to incorporate the devastating direct, and indirect, worldwide impacts from the COVID-19 pandemic on population health. Understanding how the study differs from its predecessors is important to inform the innumerable secondary research opportunities from its use. Population Health Metrics prioritise the appraisal of innovative GBD research that moves the dial beyond reporting population health trends already available from the variety of publicly available GBD data visualisations and tools. Burden of disease studies remain a prominent area of research that contribute towards Population Health Metrics achieving its aim of publishing research that informs advances in the science of population health assessment internationally, nationally, and locally. It also remains important that we appraise the gaps in the GBD study, particularly those which are potentially of high impact in policy-influencing discussions. Innovative local and national research has an important role to play in influencing the development of the future GBD study, as well as research which utilises GBD estimates in innovative ways to achieve positive policy impact.